Regenerative Braking Conscious Rule-Based Energy Management Strategy for Semi-Active Hybrid Energy Storage Systems for Electric Vehicles (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Hybrid Energy Storage Systems (HESS) function as a solution to extend the lifespan of battery packs by maintaining a low charge/discharge rate. The integration of HESS in electric vehicles (EVs) is facilitated by supercapacitors (SC), known for their safe operation even under harsh conditions. The widely adopted rule-based power follower energy management strategy (EMS) is employed to control and restrict battery discharge within a defined range with SC support. Additionally, it charges the SC to accommodate regenerative energy, but it often neglects exploring the SC voltage set reference. This study investigates the SC voltage reference point and introduces a method to generate the reference point by equating the SC energy with the available kinetic energy in the moving vehicle. The proposed method was simulated and compared against the benchmark method using a portion of the medium segment Worldwide Harmonized Light Vehicles Test Procedure (WLTP) driving cycle. The results demonstrate a more stable discharge power for the battery bank, accompanied by improvements in battery voltage stability. The root mean square (RMS) battery current values were found to be 43.68 A and 42.92 A for the benchmarked and proposed methods, respectively, indicating a slight improvement of about 1%. Furthermore, the proposed method reduces the voltage deviation from 2.73% to about 2.57%, showcasing an additional positive outcome. These findings suggest that dynamically adjusting the SC voltage based on kinetic energy can enhance battery life and stability in EVs, offering a promising direction for future research and development of EMS.
Keywords: Hybrid Energy Storage System; Regenerative Braking; Supercapacitor; Supercapacitor voltage reference